MEWUJUDKAN SITUBONDO INKLUSI: PENINGKATAN PEMAHAMAN TENTANG WACANA DISABILITAS MELALUI PRODUKSI FILM - Rijadi, Arief; Hidayatullah, Panakajaya (Jurnal Pengabdian Masyarakat Khatulistiwa, 2023)
ABSTRACTThis community service activity aims to support the creation of Situbondo Regency as an inclusion city. The service team of Jember University collaborated with the disability pillar care Program implemented by PPDi Situbondo. The concrete steps of this service activity include (1) reviewing the development of disability issues and discourses to make it into a film Concept, (2) realizing the concept into a fiction film script with the theme of disability. The implementation method is carried out in three stages, namely the preparatory stage, the mentoring and production stage, the evaluation stage. The results of the implementation of this service have realized two stages, namely the first, building a commitment with partners (PPDi Situbondo) through FGD activities. FGD results have been obtained information that there are still various problems in realizing Situbondo as a disability-friendly city. The results of the FGD were finally focused on the field of Education. This is in accordance with the results of the FGD that PPDiS partners prefer to direct disability-friendly environmental education programs to the people of Situbondo Regency. The second stage is to socialize the draft of the disability fiction film script through FGD with partners. The second phase of the FGD focused on discussing the draft script for disability fiction films by discussing characters and character figures. It also discusses the scenario of disability fiction films. The results of the FGD have produced several characters and characters consisting of six characters and a fictional disability film scenario.Keywords: Situbondo inclusion, fiction film, disabilityABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk mendukung terciptanya Kabupaten Situbondo sebagai kota inklusi. Tim pengabdian Universitas Jember berkolaborasi dengan Program Peduli Pilar Disabilitas yang dilaksanakan oleh PPDi Situbondo. Langkah–langkah konkret kegiatan pengabdian ini antara lain, (1) penelaahan perkembangan isu dan wacana disabilitas untuk mewujudkannya ke dalam konsep film, (2) merealisasikan konsep menjadi naskah film fiksi bertema disabilitas. Metode pelaksanaan dilakukan dalam tiga tahap, yaitu tahap persiapan, tahap pendampingan dan produksi, tahap evaluasi. Hasil pelaksanaan pengabdian ini telah mewujudkan dua tahap yaitu pertama, membangun komitmen dengan mitra (PPDIS Situbondo) melalui kegiatan FGD. Hasil FGD telah diperoleh informasi bahwa masih ditemukan berbagai masalah dalam mewujudkan Situbondo sebagai kota ramah disabilitas. Hasil FGD tersebut akhirnya difokuskan pada bidang pendidikan. Hal ini sesuai dengan hasil FGD bahwa mitra PPDIS lebih mengarahkan program pendidikan lingkungan ramah disabilitas kepada masyarakat Kabupaten Situbondo. Tahap kedua, melakukan sosialisasi draf naskah film fiksi disabilitas melalui FGD dengan pihak mitra. FGD tahap kedua difokuskan pada pembahasan draf naskah film fiksi disabilitas dengan mendiskusikan tokoh dan karakter tokoh. Selain itu juga membahas skenario film fiksi disabilitas. Hasil FGD telah menghasilkan beberapa tokoh dan karakternya yang terdiri atas enam tokoh serta skenario film fiksi disabilitas.Kata Kunci: Situbondo inklusi, film fiksi, disabilitas